Employing Mobile Technologies to Investigate the Association Between Abstraction Skills and Performance in Environmental Studies in Early Primary School - Kanaki, Kalliopi; Kalogiannakis, Michail; Poulakis, Emmanouil; Politis, Panagiotis (International Journal of Interactive Mobile Technologies (iJIM), 2022)
In the modern digital era, the impressive development of mobile technologies has entailed the reformation of orientations, dispositions and stances in education, changing the dominant approaches to learning. In this article, we introduce the novel idea of the synergistic development of computational thinking skills and environmental awareness in the early primary school years, by employing mobile technologies.